Case report: Duodenal obstruction caused by gastroduodenal artery pseudoaneurysm with hematoma: an unusual case and literature review - Zhou, Yan-Yuan; Wang, Shao-Chung; Seak, Chen-June; Huang, Shu-Wei; Cheng, Hao-Tsai (Frontiers in Medicine, 2023)
Visceral artery pseudoaneurysm is a rare disease that most commonly occurs in male patients in their 50s, with gastroduodenal artery (GDA) pseudoaneurysm accounting for only 1.5% of these. The treatment options generally include open surgery and endovascular treatment. In 40 cases of GDA pseudoaneurysm from 2001 to 2022, endovascular therapy was the mainstay of treatment in 30 cases, and most of them (77%) were treated by coil embolization. Our case report describes a 76-year-old female patient with a GDA pseudoaneurysm, which was treated by endovascular embolization using liquid embolic agent N-butyl-2-cyanoacrylate (NBCA) alone. This is the first time this treatment strategy has been used for GDA pseudoaneurysm. We demonstrate a successful outcome with this unique treatment. The successful experience of our case may provide a new treatment strategy for this rare disease.